Using Micro-Synteny for Phylogenetic Inference and Analysis - Casey, Dearbhaile (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Genetics, 2024)
Phylogenetics is the study of the evolutionary relationships and history of groups of organisms. Over the past twenty years, the burgeoning number of sequenced genomes has revolutionised the field of phylogenetics taking it from morphological cladistics, in which organisms are grouped together based on shared, derived morphological characteristics (synapomorphies) to more exact molecular methods. Most commonly, phylogenetic inference utilises molecular alignments, arranging the genetic sequences in such a way that homologous positions are matched, allowing similarities and differences to be quantified. In this work, we focus on a novel method of inference that focuses on examining the changes in local gene positions, known as micro-synteny, across different species as a phylogenetic character. We underscore the significance of micro-synteny, its conservation, and its movement in aiding the determination of evolutionary relationships. Genomes are dynamic and appreciation of this in our research is paramount for unravelling the true genetic history of lineages. In this thesis I hope to show that incorporating synteny and synteny evolution into phylogenetic analyses can build upon previous frameworks and help in solving many unanswered questions in animal evolution.
APPROVED
Keywords: micro-synteny; phylogenetics; rediploidization; paddlefish; sturgeon; genes; collinearity; genome; genetics